Les acteurs ordinaires face aux images de la monarchie. Autour de l’iconoclasme révolutionnaire dans les Calabres (1848) - Pierre-Marie Delpu (Mélanges de la Casa de Velázquez)
Based on a regional case, this contribution aims to highlight a modality of collective protest, regicidal iconoclasm, which, despite its recurrence in the revolutions of the nineteenth century, was not necessarily recognized by contemporaries in its political dimension. During the revolution of 1848, when the entry of the southern masses into politics accelerated, the destruction of images representing the monarchy took on a considerable scale, which the policial and judicial documentation allows us to analyse. This study focuses on the repertoires of action in which the iconoclastic acts were carried out (destructive gestures, staging the death of the king, regicidal insults), in order to grasp their political significance. Although they were not always accompanied by a coherent political project, they testify to local popular demands with regard to a centralized national government considered distant and unsuitable.